Determinants of Fruits and Vegetables Consumption among Primary School Students: A Path Analysis Evidence - Siti Shafridha Hidayah; Eti Poncorini Pamungkasari; Endang Sutisna Sulaeman (Masters Program in Public Health, Sebelas Maret University, 2019)
Background: Around 3.9 million deaths worldwide in 2017 were caused by a lack of fruit and vegetable consumption. Consumption of fruits and vegetables in Indonesia is still less than recommended by World Health Organization. This study aimed to examine determinants of fruits and vegetables consumption among primary school children.Subjects and Method: This was an analytic observational study with a cross sectional design. The study was conducted at 25 elementary schools in Tegal, Central Java, from April to May 2019. A sample of 200 primary schools was selected by simple random sampling. The dependent variable was fruits and vegetables consumption. The independent variables were gender, knowledge, economic status, fruits and vegetables availability, sources of information, food preference, food selection, and parental role. The data were collected by food frequency questioner (FFQ) and questionnaire. The data were analyzed by path analysis. Results: Fruit consumption was directly influenced by male gender (b=-0.99; 95% CI= -1.86 to -0.12; p=0.025), knowledge (b= 0.92; 95% CI= 0.04 to 1.79; p=0.039), economic status (b=1.96; 95% CI= 1.09 to 2.83; p<0.001), fruits and vegetables availability (b= 0.92; 95% CI= 0.07 to 1.76; p= 0.034), source of information (b= 0.92; 95% CI= 0.01 to 1.82; p= 0.047), food selection (b= 1.77; 95% CI= 0.01 to 3.54; p= 0.049), and parental role (b= 1.19; 95% CI= 0.27 to 2.13; p=0.012). Vegetables consumption was directly influenced by male gender (b= -0.71; 95% CI= -1.37 to -0.05; p= 0.035), economic status (b= 0.81; 95% CI= 0.05 to 1.56; p=0.036), fruits and vegetables availability (b=0.98; 95% CI= 0.33 to 1.64; p=0.003), and parental role (b= 0.95; 95% CI= 0.19 to 1.69; p= 0.013). Fruit and vegetable consumption was indirectly influenced by gender, food preference, and economic status.Conclusion: Fruit consumption is directly influenced by male gender, knowledge, economic status, fruits and vegetables availability, source of information, food selection, and parental role. Vegetables consumption is directly influenced by male gender, economic status, fruits and vegetables availability, and parental role. Fruit and vegetable consumption is indirectly influenced by gender, food preference, and economic status.Keywords: consumption, fruits and vegetables, path analysisCorrespondence: Siti Shafridha Hidayah. Masters Program Public Health, Universitas Sebelas Maret. Jl. Ir. Sutami 36A, Surakarta 57126, Central Java. Email: shafridhahidayah@yahoo.com. Mobile: +6287737376507.Journal of Health Promotion and Behavior (2019), 4(1): 64-75https://doi.org/10.26911/thejhpb.2019.04.01.07